A Review on Energy Saving Techniques for Wireless Local Area Networks (WLAN) - W Muhamad, Wan Norsyafizan; Y.Khan, Jamil; Brown, Jason; Naim, Nani Fadzlina (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Energy efficiency issues is becoming paramount important with the increasing number of internet based application deployment. With the growth of internet application deployment, there is a huge increase in the number of WiFi enabled devices which leads to increased deployment of WLANs. Increased energy consumption has several detrimental effects. In general, it leads to a rise in greenhouse gases as well as contributes to higher cost of business operation. Specifically, for WLANs since the user devices are mostly battery operated which limits the useful lifetime of a terminal, thus managing energy efficiently is extremely important in such devices to prolong the battery life. This paper presents a comprehensive review for energy saving approaches proposed for the WLAN